Strategi dan Inovasi Guru dalam Pembelajaran Bahasa Indonesia di Era 5.0 - Sinta Zakiyah; Putri Akhiriyani Siregar; Aufa Yasifa (BADAN PENERBIT STIEPARI PRESS, 2023)
This observation was carried out with the aim of identifying more about teacher strategies and innovations in learning Indonesian. This research uses a methodology appropriate to the topic to be discussed, which includes types of research methods, data collection techniques, and problem boundaries. Teachers are the foundation of education, but in the era of society 5.0 the role of the teacher has shifted with technological developments. Learning innovation is an important thing and must be done immediately by the teacher in order to improve the quality of learning that is more interactive, integrated, and meaningful. Interesting and effective learning strategies are needed so that the teacher still has the role as an agent of knowledge transfer. There are five learning strategies that can be applied in the era of society 5.0, namely (1) helping students learn, (2) giving students opportunities to develop and achieve, (3) strengthening character education, (4) technology literacy, (5) becoming an effective teacher.